Pathophysiology of Preeclamsia - Hudila Rifa Karmia; Joserizal Serudji (Universitas Andalas, 2022)
The uncertainty of the etiology and underlying mechanisms of the pathophysiology of this disease makes causal structuring and primary prevention of preeclampsia impossible, making it difficult to control morbidity and mortality, both maternal and perinatal. From the many theories on preeclampsia, the disease can be classified into Placental preeclampsia, maternal preeclampsia, and Vascular Disorders of Pregnancy (VDP). Increased inflammatory response to placental factors, excessive inflammatory response to placental factors, and primary vascular disorders are the basis of distinction and also the basis of pathophysiology among the three forms of preeclampsia.